Dehydroleucodine exerts an antiproliferative effect on human Burkitt’s lymphoma Daudi cells via SLC7A11-mediated ferroptosis - Shen, Rui; Cheng, Fang; Guo, Rui; Wang, Wenjing; Yang, Xiaolong; Chen, Yemiao; Chen, Yaokai (Frontiers in Pharmacology, 2025)
BackgroundBurkitt’s lymphoma (BL) is a rare, highly aggressive B-cell non-Hodgkin’s lymphoma known for rapid proliferation. While most patients respond well to intensive chemotherapy, those who are older, have comorbidities, or develop therapy resistance show limited outcomes.PurposeThis study aims to evaluate the in vitro anti-tumor activity of dehydroleucodine (DhL), a novel plant-derived chemotherapeutic agent, against BL cells and to elucidate the molecular mechanisms underlying its effects.MethodsA screening of 42 plant-derived small molecules identified DhL as a potent inhibitor of BL growth. We evaluated DhL’s effects on cell cycle progression, apoptosis, and ferroptosis pathways using cell viability assays, flow cytometry, transcriptomic analysis, and validation experiments.ResultsDhL demonstrated robust and specific anti-proliferative effects against BL Daudi cells. Mechanistic investigations revealed that DhL exerts its effects through cell cycle modulation, induction of apoptosis, and ferroptosis. Transcriptomic analysis identified SLC7A11 as a critical regulator of DhL-mediated ferroptosis, which was further validated experimentally.ConclusionDhL shows strong potential as a novel chemotherapeutic agent for BL treatment by targeting SLC7A11-mediated ferroptosis. Further investigation is warranted to confirm its efficacy and clinical utility in diverse BL patient populations.